Brahma-Related Gene 1 Deficiency in Endothelial Cells Ameliorates Vascular Inflammatory Responses in Mice - Zhang, Yuanyuan; Wang, Huidi; Song, Mingzi; Xu, Tongchang; Chen, Xuyang; Li, Tianfa; Wu, Teng (Frontiers in Cell and Developmental Biology, 2020)
Endothelial dysfunction plays important roles in promoting the progression of disease genesis such as atherosclerosis and abdominal aortic aneurysms (AAA). In this present study, we investigated Brahma related gene 1 (Brg1), a chromatin remodeling protein, was in mouse models of diabetic atherosclerosis and abdominal aortic aneurysms focusing on its role in endothelial dysfunction. We report that compared with their wild type (WT, ApoE-/-;Brg1fl/fl) littermates, endothelium conditional Brg1 knockout mice (CKO, ApoE-/-;Brg1fl/fl;CDH5-cre) exhibited an alleviated phenotype of diabetic atherosclerosis. Immunohistochemical staining and real-time PCR analysis demonstrated less macrophages recruitment with a reduction of vascular inflammatory in CKO mice compared with WT mice. Further research in Ang II-induced AAA model revealed that BRG1 deficiency had the protective effects on endothelium conditional Brg1 deletion, evidenced by down-regulation of pro-inflammatory mediators (IL-1β, not TNF-α and IL-6) in the vessels of CKO mice compared with WT mice. In Ea.hy926 cell lines, Anti-Brg1 siRNA and PFI-3 treatment obviously alleviated TNF-α induced inflammatory response, and further research demonstrated that the Brg1 inhibition in endothelial cells not only decrased c-fos expression，but also blocked the c-fos translocation into nucleic. In conclusion, our results suggest that endothelial Brg1 deficiency may protect the mice from diabetic atherosclerosis and abdominal aortic aneurysms via inhibiting inflammatory response in vessels.